1997
DOI: 10.1002/(sici)1097-0320(19970815)30:4<192::aid-cyto6>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of posttreatment spermatogenesis in patients with testicular cancer by flow cytometric sperm chromatin structure assay

Abstract: The hypothesis to be tested was that abnormal sperm chromatin structure is related to disturbed spermatogenesis in patients with testicular cancer. After orchiectomy but before further treatment (“pretreatment”), semen samples from 39 patients with testicular cancer were analyzed for sperm concentration by light microscopy and by the sperm chromatin structure assay (SCSA). In 28 patients assessment of sperm concentration was repeated 12–26 months after orchiectomy (“posttreatment”). The pretreatment SCSA resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…These observations strengthen the conclusion that higher DFI% seen in cancer patients compared with controls is because of the cancer disease rather than to the procedure of cryopreservation or selection of controls. The slightly increased DFI% in HL and TGCC patients prior to chemo-or radiotherapy is in accordance with previous studies (Fossa et al, 1997;Gandini et al, 2000;O'Donovan, 2005;Spermon et al, 2006;O'Flaherty et al, 2008) but opposite to our own earlier results (Stahl et al, 2006). However, our previous results were based on a small group of TGCC patients.…”
Section: Discussionsupporting
confidence: 81%
“…These observations strengthen the conclusion that higher DFI% seen in cancer patients compared with controls is because of the cancer disease rather than to the procedure of cryopreservation or selection of controls. The slightly increased DFI% in HL and TGCC patients prior to chemo-or radiotherapy is in accordance with previous studies (Fossa et al, 1997;Gandini et al, 2000;O'Donovan, 2005;Spermon et al, 2006;O'Flaherty et al, 2008) but opposite to our own earlier results (Stahl et al, 2006). However, our previous results were based on a small group of TGCC patients.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies have documented that conditions like abstinence time, fever, temperature alterations, seasonal changes, smoking, medication and exposure to environmental hazards can alter sperm DNA integrity (Fossa et al, 1997;Spano et al, 1998;Sanchez-Pena et al, 2004;Rignell-Hydbom et al, 2005); although, no association between sperm DNA fragmentation and the length of abstinence time was observed by De Jonge et al (2004). For our study, patients who reported changes in medication or any significant illness or infection between different semen samples were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Young men with cancer (eg, Hodgkin lymphoma and testicular cancer) typically have poor semen quality and sperm DNA damage even prior to cancer-specific therapy (O'Flaherty et al, 2008). They then experience cumulative dose damage during therapy (chemotherapy, radiation), often rendering them completely sterile (Fossa et al, 1997;Morris, 2002). The recovery of spermatogenesis may occur months to years after therapy, but evidence of sperm DNA damage may often persist beyond that period (Fossa et al, 1997).…”
Section: Etiology Of Sperm Dna Damagementioning
confidence: 99%
“…They then experience cumulative dose damage during therapy (chemotherapy, radiation), often rendering them completely sterile (Fossa et al, 1997;Morris, 2002). The recovery of spermatogenesis may occur months to years after therapy, but evidence of sperm DNA damage may often persist beyond that period (Fossa et al, 1997). Patients who are scheduled to undergo definitive cancer therapy (surgery, chemotherapy, and/or radiation) are strongly encouraged to cryopreserve sperm for future use (Lee et al, 2006).…”
Section: Etiology Of Sperm Dna Damagementioning
confidence: 99%